Poetry and the question of modernity from Heidegger to the present - Cooper, Ian 1979- (Routledge, 2020)
"Interest in Martin Heidegger was recently reawakened by the revelations, in his newly published 'Black Notebooks', of the full terrible extent of his political commitments in the 1930s and 1940s. The revelations reminded us of the dark allegiances co-existing with one of the most profound and important philosophical projects of the twentieth century - one that is of incomparable importance for literature and especially for poetry, which Heidegger saw as embodying a receptiveness to Being and a resistance to the instrumental tendencies of modernity. Poetry and the Question of Modernity from Heidegger to the Present is the first extended account of the relationship between Heidegger's philosophy and the modern lyric. It argues that some of the best-known modern poets in German and English, from Paul Celan to Seamus Heaney and Les Murray, are in deep imaginative affinity with Heidegger's enquiry into finitude, language, and Being. But the work of each of these poets challenges Heidegger because each appeals to a transcendence, taking place in language, that is inseparable from the motion of encounter with embodied others. It is thus poetry which reveals the full measure of Heidegger's relevance in redefining modern selfhood, and poetry which reveals the depth of his blindness"--
Keywords: Heidegger, Martin / 1889-1976 / Knowledge / Poetry; Celan, Paul / Criticism and interpretation; Murray, Les A. / 1938-2019 / Criticism and interpretation; Heaney, Seamus / 1939-2013 / Criticism and interpretation; Poetry; Poetry, Modern / History and criticism; Transcendence (Philosophy); Poetry / Religious aspects